2008
DOI: 10.1523/jneurosci.1135-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Functional Topography and Integration of the Contralateral and Ipsilateral Retinocollicular Projections ofEphrin-A−/−Mice

Abstract: ؊/؊ but disorganized in ephrin-A2/A5 ؊/؊ mice. The lack of integration of binocular input resulted in specific visual deficits, which could be reversed by occlusion of one eye. The discrepancy between anatomical and functional topography in both the ipsilateral and contralateral projections implies suppression of inappropriately located terminals. Moreover, the misalignment of ipsilateral and contralateral visual information in ephrin-A2/A5 ؊/؊ mice suggests a role for ephrin-As in integrating convergent visua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(88 citation statements)
references
References 52 publications
5
83
0
Order By: Relevance
“…2A). An exception was ephrin-A5, which elicited a very strong response but has only minimal expression on injured muscle fibers; we hypothesize that this might be due to potential functional redundancy of ephrin-A5 with ephrin-A2 (Haustead et al, 2008).…”
Section: Muscle Satellite Cells Respond Specifically and Repulsively mentioning
confidence: 96%
“…2A). An exception was ephrin-A5, which elicited a very strong response but has only minimal expression on injured muscle fibers; we hypothesize that this might be due to potential functional redundancy of ephrin-A5 with ephrin-A2 (Haustead et al, 2008).…”
Section: Muscle Satellite Cells Respond Specifically and Repulsively mentioning
confidence: 96%
“…Similarly, repulsive signalling in axon guidance may provide benefits in patterning axonal projections. In a purely attractive environment, connections would form in the first available ‘attractive’ location, increasing the probability of projection errors as observed in ephrin A -/- mice [65,66]. The presence of repulsive cues may promote growth cone motility and searching within a target region, allowing other processes such as contributions from other guidance cues or activity-dependent mechanisms to come into play.…”
Section: Repulsive Signalling: How and Why?mentioning
confidence: 99%
“…Possibilities include that these proteins may contribute to cortical arealisation in ways that remain to be determined. It is interesting to note that the individual variation in cortical laminar disruption in ephrin triple knockout mice is reminiscent of the defects in axon guidance in the visual system of ephrin A single, double and triple knockout mice, which are detected in only a proportion of animals and affect only some cells [65,66,97,98,99]. This individual variation may reflect the inherent ability of Eph-ephrin signalling to integrate with other molecular cues, as well as with activity-dependent mechanisms [30,100].…”
Section: Eph-ephrin Interactions In Cortical Developmentmentioning
confidence: 99%
“…For example, in vitro, contralaterally and ipsilaterally projecting axons do not respond differentially to inhibition of EphA signaling (as they do for EphB signaling) (Marcus et al, 2000) and, in vivo, no evidence for abnormal chiasm guidance have been observed in Ephrin-A mutant mice (Feldheim et al, 2000;Haustead et al, 2008). Additionally, the Slit proteins, through their Robo receptors, channel RGC axons into their normal paths and regulate their fasciculation, but normal ipsilateral projections form in the Slit1;Slit2 mutant mice (Plump et al, 2002).…”
Section: Boc Is a Bifunctional Axon Guidance Receptor For Shhmentioning
confidence: 99%